2013
DOI: 10.1007/s10750-013-1721-4
|View full text |Cite
|
Sign up to set email alerts
|

Early beak development in Argonauta Nodosa and Octopus Vulgaris (Cephalopoda: Incirrata) paralarvae suggests adaptation to different feeding mechanisms

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In contrast, jaws with a calcareous covering and a robust radula, as found in nautilids, have been suggested to be suited for a scavenging life style. Moreover, some authors have suggested that the beaks of para‐larvae of recent octopods, argonauts and some squid show features that facilitate prey ingestion (Franco‐Santos et al, 2013; Franco‐Santos & Vidal, 2014, 2020). Moreover, diet can vary greatly during ontogeny in ommastrephid squid, ranging from detritivory in paralarvae to carnivory in adults (Fernández‐Àlvarez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, jaws with a calcareous covering and a robust radula, as found in nautilids, have been suggested to be suited for a scavenging life style. Moreover, some authors have suggested that the beaks of para‐larvae of recent octopods, argonauts and some squid show features that facilitate prey ingestion (Franco‐Santos et al, 2013; Franco‐Santos & Vidal, 2014, 2020). Moreover, diet can vary greatly during ontogeny in ommastrephid squid, ranging from detritivory in paralarvae to carnivory in adults (Fernández‐Àlvarez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…General beak appearance was similar to that described for similar sized O. vulgaris paralarvae reared in Vigo, Spain (Franco‐Santos et al . ), except for the absence of a small slit in the rostrum (whose protrusion is slightly less concave) in the LJ and a colouration pattern slightly more spread out in the hood region of both jaws.…”
Section: Resultsmentioning
confidence: 93%
“…In this study, only the UJ of O. vulgaris paralarvae was used for indentifying growth increments and stress marks because the LJ has very conspicuous teeth in the counting area (which makes it very difficult to identify and count increments), which is also shorter (anterior‐posterior axis) in the LJ. When considering species other than O. vulgaris , however, it must be considered that the level of rostrum development varies according to species (for examples on squid and octopod species, see Franco‐Santos & Vidal ; and Franco‐Santos, Iglesias, Domingues & Vidal , respectively) and that the structure might not be suitable for growth increment analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptions of the paralarvae of A. hians (1.0 mm) are scarcer [11,43,44], where some authors describe2 + 2 in the funnel and in the VHCP [24], an arrangement of 4 chromatophores (rectangle shape) on the dorsal side of the head [26], and 4 + 4 in the DHCP [24,[40][41][42]. Although the paralarvae of Argonauta nodosus were reported by [45,46], there is no morphological description of them.…”
Section: Discussionmentioning
confidence: 99%